Characterizing and designing promoter of gene \(ZmDREB2.7\) into plant expression vector - Thu Hue, Huynh Thi; Quang Ha, Dao; Thuy Duong, Nguyen (Academia Journal of Biology, 2022)
In the regulation of gene expression, particularly abiotic-stress tolerance characteristics in plants, inducible promoters play an essential role in ensuring the endurance and productivity of crops. In several previous studies, the ZmDREB2.7 gene and some DNA polymorphisms in its promoter have been shown to enhance drought tolerance traits in maize (Zea mays L.). With the goal of creating a strong drought-tolerant promoter region derived from maize, in this study, the 1 kilobase 5’-upstream region of the ZmDREB2.7 coding sequence from the drought resistant maize line Tevang1 was isolated and characterized. Essential putative cis-regulatory elements (as TATA box or CAAT box) and other elements that regulate drought tolerant properties (as RY/G box, ABRE element or MYB core) were investigated. After that, we designed the transgenic plant vector containing the isolated promoter and the ZmDREB2.7 gene which were isolated in our earlier study. The promoter segment was removed 20 nucleotides ahead of the transcription start site and transferred into the recombinant pZY vector containing the ZmDREB2.7 gene. In conclusion, we created a recombinant vector containing the modified ZmDREB2.7 promoter and the ZmDREB2.7 gene segment derived from maize. This is a promising resource for the creation of a transgenic cultivar with effective resistance to dry stress in the future. Besides, we will keep on examining other potential genetic regions and promoters to diversify sources of genetic materials as well as understand deeper the stress-resistant transgenic plants.